Persepsi Peternak Terhadap Keberlanjutan Usaha Sapi Potong (Kasus di Desa Kondangjajar Kecamatan Cijulang Kabupaten Pangandaran Jawa Barat) - Yunasaf, Unang; Alim, Syahirul; Rahayu, Desti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research was conducted in the Wiru Nunggal and Putra Nusa beef cattle farmers groups, Kondangjajar Village, Cijulang District, Pangandaran, West Java. This research aims to determine the characteristics of farmers and the farmers' perceptions of the sustainability of the beef cattle business, as well as to analyze the relationship between these two variables. The research was conducted using a survey method involving 38 respondents taken by census. The data obtained were analyzed using Spearman Rank correlation. The results of the research show that: (1) the characteristics of farmers are that most of them are in the middle adult category (41-60 years), their education level is in the low category (primary school), their farming experience is in the medium category (8-14 years). , the number of livestock owned is in the low category (1-3 livestock) and the number of family dependents is in the small category (1-2 people). (2) The farmer's perception of the sustainability of the beef cattle business is included in the medium category, which means that the farmer's perception of the sustainability of the beef cattle business is quite good. (3) Farmer characteristics that have a positive and significant relationship to the perception of sustainability of beef cattle farming are age, level of education, and number of livestock owned.